Speech Acts in Social Media Fraud: Manipulative Communication Strategies on WhatsApp and Facebook - Lailiyah, Nur; Galuh Kirana Dwi Areni; Favorita Kurwidaria; Setyo Prasiyanto Cahyono; Monika Widyastuti Surtikanti; Farida Indri Wijayanti (Universitas Negeri Semarang, 2025)
This research aims to investigate the role of speech acts in fraudulent activities on social media platforms, particularly WhatsApp and Facebook, through a pragmatic framework. The primary goal is to identify the manipulative communication strategies employed by perpetrators to deceive and inluence victims. A qualitative-descriptive methodology was adopted, with data collected from conversation screenshots and communication recordings sourced from victims' case reports in WhatsApp and Facebook (n = 39). The data were analyzed using the speech act theory by Austin and Searle, along with Grice’s concept of implicature. The findings reveal that directive and commissive speech acts are central to the perpetrators' manipulative strategies, often combined with hidden implicatures intended to create a sense of urgency, establish false trust, and foster emotional dependency in victims. These findings contribute to a deeper understanding of the communicative tactics used in social media fraud. Ultimately, this research offers valuable insights into the dynamics of online deception, highlighting the importance of enhancing digital literacy and advancing strategies for cybercrime prevention. This study also provides a foundation for further research on communication patterns in digital fraud.